INFLUENCE OF GAMIFICATION ON KHAN ACADEMY IN BRAZILIAN HIGH SCHOOL - Tenório, Marcos Mincov; Lopes, Rui Pedro; Góis, Lourival Aparecido; Junior, Guataçara Dos (PUPIL: International Journal of Teaching, Education and Learning, 2018)
This article approaches current pedagogical practices in the national guidelines, related to the use of information and communication technologies. We report the actions taken in a compulsory curricular internship of the bachelor’s degree in informatics of the UTFPR-Francisco Beltrão Campus. The internship student performs observation and experiment inside a first-year high school classroom and suggest the use of an e-learning tool to support learning, reinforce classroom concepts and motivate students to perform extra classroom activities. Gamification technique was suggested seeking to increase students’ motivation, engagement and commitment. To address this issue, the e-learning system of Khan Academy was selected and their structure and functions was studied, serving as technological support for gamification actions. An experiment was proposed to obtain results regarding the Khan Academy and gamification usage inside a classroom environment. When applied, Khan Academy has proved to be a promising tool regarding new opportunities and ways of engaging student especially with the built-in gamified structures. Yet, the role of teachers in motivating students to perform extra-classroom activities in the pursuit of knowledge remains crucial, even with the use of online tools and gamification technique.